1995
DOI: 10.2337/diacare.18.6.843
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Normalizing Fasting Glucose With Bedtime NPH Insulin Alone in NIDDM

Abstract: NPH insulin given at bedtime in amounts sufficient to achieve a normal FPG level does not cause excessive or severe hypoglycemia and does lead to good glycemic and lipid control in NIDDM. Bedtime insulin therapy also is accompanied by improved insulin secretion and insulin sensitivity. We conclude that a single dose of insulin alone at bedtime merits consideration as a therapeutic strategy in patients with poorly controlled NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 29 publications
5
42
1
Order By: Relevance
“…These conclusions are further supported by the observations of Cusi et al [40] who noted that the average intermediate-acting bedtime postabsorptive dose required to normalize fasting plasma glucose by the following morning was about 65 U. This amount of insulin is far greater than the amount needed to normalize fasting plasma glucose by intravenous administration.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These conclusions are further supported by the observations of Cusi et al [40] who noted that the average intermediate-acting bedtime postabsorptive dose required to normalize fasting plasma glucose by the following morning was about 65 U. This amount of insulin is far greater than the amount needed to normalize fasting plasma glucose by intravenous administration.…”
Section: Discussionsupporting
confidence: 74%
“…Anecdotal information from the Texas Diabetes Institute suggests that U500 insulin has a time-course action similar to that of NPH. In agreement with Cusi et al [40], we also note that normalization of fasting morning glucose concentration results in significantly better control of glucose levels throughout the day [47]. It is also relevant that Garvey et al [48] noted that 150 U of regular insulin administered by continuous subcutaneous infusion was necessary to normalize fasting plasma glucose in type 2 diabetic patients.…”
Section: Insulin Typesupporting
confidence: 80%
See 1 more Smart Citation
“…Although insulin therapy typically produces modest weight gain, rosiglitazone led to twice as much weight gain (3.0 kg) as insulin glargine (1.6 kg). As previously demonstrated with insulin treatment (17)(18)(19)(20), patients treated with insulin glargine resulted in a significantly improved serum lipid profile compared with those treated with rosiglitazone…”
Section: Treatment Dose and Costsmentioning
confidence: 53%
“…In a Veterans' Administration cooperative study of 153 men with type 2 diabetes, comparing standard with intensive insulin treatment, the former began on ϳ20 units daily, increasing to ϳ50 units daily, while the latter began with ϳ30 and increased to ϳ80 units daily, with A1C remaining around 9.5% in the former group while decreasing to Ͻ7% in the intensive group (23). Similarly, a study with aggressive administration of NPH insulin at bedtime reduced A1C from 9.5 to 7.2%, at a mean daily dose of 85 units (24). Reviewing a large group of studies of the efficacy of insulin in type 2 diabetic patients, Nathan showed that A1C levels around 7% are relatively readily achieved, typically with insulin doses of 0.6 -0.9 units/kg body wt daily, although Nathan noted that in the Kumamoto Study, carried out in Japan, 0.44 units ⅐ kg Ϫ1 ⅐ day Ϫ1 was required, suggesting the importance of ethnic differences.…”
mentioning
confidence: 99%